O silêncio de Deus diante do sofrimento humano na teologia de Bruno Forte - Vian, Ludinei Marcos (2014)
The paper focus the thematic: The Silence of God face human suffering, according to Bruno Forte theology. Object of study is the silence of God and human suffering. The objectives are: to present the theology of Bruno Forte, answer why the silence of God in the face of human suffering and demonstrate the participation and presence of God in human history center. The method is literature. The results are found in Bruno Forte writes about Theology and Company, Memory and Prophecy, and the writing on the Trinity manifested as Silence and Word Meeting. These results are obtained from a theology of the cross that is sure that God is in distress. The certainty of the victory of life over death. It confirms that God is not absent in silence, but it's company. From this certainly opens up the prospect of seeing the face of the suffering God's presence.